Societal attention toward extinction threats: a comparison between climate change and biological invasions - Jarić, Ivan; Bellard, Céline; Courchamp, Franck; Kalinkat, Gregor; Meinard, Yves; Roberts, David L; Correia, Ricardo A (Scientific reports, 2020)
Public attention and interest in the fate of endangered species is a crucial prerequisite for effective conservation programs. Societal awareness and values will largely determine whether conservation initiatives receive necessary support and lead to adequate policy change. Using text data mining, we assessed general public attention in France, Germany and the United Kingdom toward climate change and biological invasions in relation to endangered amphibian, reptile, bird and mammal species. Our analysis revealed that public attention patterns differed among species groups and countries but was globally higher for climate change than for biological invasions. Both threats received better recognition in threatened than in non-threatened species, as well as in native species than in species from other countries and regions. We conclude that more efficient communication regarding the threat from biological invasions should be developed, and that conservation practitioners should take advantage of the existing attention toward climate change.
Keywords: Introduced Species; klimatické změny; extinkce biologická; Endangered Species; Animals; Public Opinion; zavlečené druhy; Extinction, Biological; Climate Change; veřejné mínění; ohrožené druhy; Conservation of Natural Resources; zachování přírodních zdrojů; zvířata